1993
DOI: 10.1111/j.1752-0606.1993.tb00998.x
|View full text |Cite
|
Sign up to set email alerts
|

Dysphoria and Marital Discord: Are Dysphoric Individuals at Risk for Marital Maladjustment?

Abstract: The effect of dysphoria on husbands' and wives' later marital adjustment was examined in a sample of 264 white couples about to marry who responded to advertisements. Relationship satisfaction and level of dysphoria were assessed in both spouses prior to marriage, 6 months after marriage, and 18 months after marriage. Premarital dysphoria was associated with later marital dissatisfaction. Husbands' premarital dysphoria, regardless of chronicity, was associated with greater deterioration in both their own and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
1
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 28 publications
5
57
1
1
Order By: Relevance
“…Analyses of neurotic individuals, for example, reveal not only that they experience higher numbers of negative encounters on a daily basis but that they are more distressed and that their distress lasts longer after a negative encounter, compared with less neurotic individuals (Bolger and Schilling, 1991;Bolger and Zuckerman, 1995). The influence of the individualist view of marriage extends to the present day in research that examines such enduring characteristics as psychopathology (e.g., Beach and O'Leary, 1993), personality (e.g., Kelly and Conley, 1987), and attachment style (e.g., Hazan and Shaver, 1994) for their associations with marital satisfaction.…”
Section: Perspectives On Marital Satisfactionmentioning
confidence: 94%
“…Analyses of neurotic individuals, for example, reveal not only that they experience higher numbers of negative encounters on a daily basis but that they are more distressed and that their distress lasts longer after a negative encounter, compared with less neurotic individuals (Bolger and Schilling, 1991;Bolger and Zuckerman, 1995). The influence of the individualist view of marriage extends to the present day in research that examines such enduring characteristics as psychopathology (e.g., Beach and O'Leary, 1993), personality (e.g., Kelly and Conley, 1987), and attachment style (e.g., Hazan and Shaver, 1994) for their associations with marital satisfaction.…”
Section: Perspectives On Marital Satisfactionmentioning
confidence: 94%
“…Other studies found that depression is related to lower marital satisfaction and warmth (Beach and O'Leary, 1993;Burns et al, 1994;O'Leary et al, 1994). Researchers have found lower marital satisfaction in battered women, although these studies did not measure chronicity or frequency of psychological abuse (Jouriles et al, 1989;Sato and Heiby, 1992).…”
Section: Domestic Violencementioning
confidence: 97%
“…13,14 Longitudinal studies also show that poor marital satisfaction predicts increases in depressive symptoms over time and co-varies with changes in depressive symptoms, and associated with increases risk of relapse within a year. [15][16][17] Marital predictors of well-being have been variously labeled as marital quality, success, happiness, satisfaction, discord, adjustment, and well-being. 18 Empirical studies link the marital variables to spouse's personal well-being.…”
Section: Discussionmentioning
confidence: 99%